In vitro propagation of high altitude plant, Heracleum wallichii DC - Manandhar, Saraswati; Pant, Bijaya (Botanica Orientalis: Journal of Plant Science, 2007)
Botanica Orientalis Vol.4(1) 2004. p.13-15